G109(P) Rotherham rapid access clinic: an ambulatory care model service evaluation. (12th March 2018) - Barraclough, H; Suri, S; Patel, D; Strawinski, E; Campbell, J
Abstract : Introduction: Ambulatory care services such as Rapid Access Clinics (RAC) improve access to specialist secondary care and potentially reduce unnecessary referrals for acute assessment/admission. Such clinics are endorsed by Standard 2 in Facing the future together for child health. XX Hospital established a consultant delivered RAC in 1995 and provides 16 thirty minute appointments weekly for children less than 16 years old. Referrals are made by fax and bookings are made 2 working days in advance. If no slots are available, the referrer is re-directed to the on-call paediatric registrar to discuss alternatives. Service evaluation: A service evaluation conducted in 2016 established the spectrum of conditions accessing the service, referral appropriateness and gave insight into the patient journey alongside parental perceptions of the service provided. It was the intention of this evaluation to identify areas for improvement, to initiate change and to ultimately reduce the growing pressure on inpatient services by enhancing the RAC service. Methodology: Data was collected prospectively for patient's attending RAC over 5 weeks using a proforma and a parental/patient questionnaire. Numeric and qualitative data was then analysed. Results: Participating consultants deemed 42.6% of RAC referrals to be appropriate and a broad range of diagnoses were seen. 49% of referrals were refused due to lack of appointment availability. 100% of patients/parents seen were happy with the consultation outcome and 93.6% were happy with how quickly their child was seen despite 52% stating their initial preference was to be seen on the day of referral. Conclusion: As a result of this service evaluation, consultant led triaging of referrals is being implemented to ensure all referrals are appropriately booked into the right clinic and to free up slots for those who are being refused. Hopefully, when re-evaluated, improvements will be seen and patient satisfaction maintained. Our presentation aims to inspire NHS trusts to set up RACs to improve efficiency of service delivery and reduce the demand on expensive inpatient assessment and overnight stay provision. Given the NHS financial climate, this type of a service is worthy of consideration.